Analisis Kesalahan Siswa Kelas V dalam Menyelesaikan Soal Tipe HOTS Berdasarkan Teori Newman - Dwiky Chandra Eka Purwanto; Latania Prara Nabilah; Mey Yustina; Nurin Zubaidah Azka; Rissa Prima Kurniawati (Universitas PGRI Madiun, 2026)
This study aims to analyze and describe the types of errors made by fifth-grade elementary school students in solving Higher Order Thinking Skills (HOTS)-based mathematics word problems on composite plane figures using Newman’s Error Analysis. The analysis stages include reading, comprehension, transformation, process skills, and encoding. This research employed a descriptive qualitative method with four students as the subjects. Data were collected through a written test in the form of HOTS essay questions and documentation of students’ work. The results showed that students’ errors were more dominant in the process skills and encoding stages. Process skills errors were caused by a lack of accuracy in performing arithmetic operations, while encoding errors occurred because students did not write conclusions, measurement units, and currency symbols completely. Therefore, students’ errors were influenced by computational accuracy and their ability to communicate final answers. These findings indicate that students need practice in rechecking calculations and writing answers according to the problem context.